(untitled) (Practitioner Research, 2023)
Gamification becomes trending to increase learning engagement. Yet it is rarely attempted by teachers for flipped classroom approach due to time constraint, the need for creativity and technology literacy. In this paper, I share my experience in gamification design to promote communication, collaboration, critical thinking, and creativity (4Cs) among students. Faced with stagnancy in using traditional cooperative strategies, I took on the challenge of designing the game “Mystery of Super Ball” for the Polymer topic, involving a group of pre-service teachers as Agents in a mystery-mission game. The study design was motivated by the gap in action research’s reflective practitioner philosophy. Data was gathered through video recording, semistructured interviews, and student reflections. The findings indicate that students demonstrated strong communication and collaboration skills while immersing themselves in their detective roles. Triangulating with quantified episodes, communication (31.01%) and collaboration (25.58%) were substantively prevalent in the students’ problemsolving tasks. However, critical thinking (22.79%) and creativity (20.62%) showed relatively lower occurrences, suggesting the need for revising my strategies. Among the 24 subconstructs of the 4Cs themes, two were minimally observed: ‘Create new and worthwhile ideas (both incremental and radical concepts)’ and ‘Analyze and evaluate major alternative points of view’, falling under creativity and critical thinking, respectively. These insightful findings strongly advocate for reevaluating the current critical essay assessment on the Polymer topic. A more innovative approach is needed, one that challenges students to showcase their creative and critical problemsolving abilities. Noteworthy, students’ perceptions of my creativity shed light on my strengths and weaknesses in game design, providing valuable insights for future research recommendations. This study highlights the importance of being a reflective practitioner, both for my pre-service student-teachers and myself as a lifelong learner.